Can the timing of hospitalization influence the outcomes of childbirth?. (30th September 2020) - Kundisova, L; Nante, N; Bardelli, S; Lorenzini, C; Alaimo, L
Abstract: Background: The timing of hospitalization of pregnant females could influence the outcomes of both mother and the baby. The aim of this study was to analyze impact of coming to hospital too early on outcomes of childbirth. Methods: A cross-sectional study was conducted in the birth center of Siena University hospital (Italy), all women that gave birth between 2017 and 2019 were included. Examined variables were: age, parity, gestational age: GA(weeks), Bishop score at admission: BS (0-13; >9 high possibility of spontaneous delivery), time to delivery:TTD (min), labor duration:LD (min), n°of interventions (induction, amniorhexis, augmentation):NI, type of birth (vaginal/caesarean section: CS/operational birth: OB), laceration, episiotomy, hematic loss: HL (ml), skin to skin:StS and initiation of breastfeeding: BR (yes/no). The females that came too early were identified if TTD >75° percentile. Analysis was performed with Stata 12. Results: A total of 758 females were analyzed (32.0±5.2years), 55.5% multiparous, average GA was 39.6±1weeks, average BS was 7.2±2.5; 63% had BS <9. Average TTD was 376.7±318.5min; 23% came too early (TTD 865.6±244), more likely primiparous (OR 3.9) and those with higher GA (OR 1.2). A negative correlation between BS and TTD was observed (Rho=-0.6), females with BS <9 had higher probability to have prolonged TTD (OR10.8). Ninety-three% had vaginal birth, 6%CS, 1%OB Average LD was 169.1±145 min, average NI was 0.64±0.93, 78% had lacerations, 7.2% episiotomy. Average HL was 299.3±282.7ml. Females with prolonged TTD had higher NI (1.2 ±1 vs 0.4±0.6), higher probability of CS (OR 3), OB (OR4.5) and episiotomy (OR3.6), lower probability of StS and BR (OR 0.9), prolonged LD (299±184 vs. 120±102) and major HL (347.2±301.8 vs 284.9±275.4). Conclusions: Our study showed an association between too early arrival to hospital and adverse maternal and fetal outcomes in terms of higher use of medical interventions that can interfere with physiological processes. Key messages: The risk of arriving too early in hospital for labor was higher in primiparous and in those with higher gestational age. The too early arrival in hospital for labor was associated within increased use of medical interventions, interfering with physiological processes.